New ingredients in food processing - Linden, G. (CRC Press, 1999)
The revolution in technology that the food industry has experienced since the Second World War has continually increased the distance between the source of ingredients and the point of conversion and consumption. This has led to the development and increasing importance of intermediate food products (IFPs), raw materials produced by primary conversion units for secondary units to process prior to consumption - IFPs have become the kit-parts of the food industry. This book is an essential reference offering a comprehensive guide to the range of IFPs available, their key benefits for the food industry (greater flexibility, functionality and more consistent quality) and the ways in which their manufacture can be tailored to the requirements of the food industry. The publication of New ingredients in food processing in English comes at a time when the food industry is under increasing pressure to produce new and innovative products, while faced with consumers who are more educated than ever before about what goes into their food. Exhaustive guide to available IFPs - range, function, application and benefitsComprehensive summary of international research into the biochemistry of IFPsExcellent link between the theoretical structure of biomolecules and their practical application in the food industry.